2016
DOI: 10.1111/mpp.12399
|View full text |Cite
|
Sign up to set email alerts
|

The role of a cytosolic superoxide dismutase in barley–pathogen interactions

Abstract: Reactive oxygen species (ROS), including superoxide ( O2·-/ HO2·) and hydrogen peroxide (H O ), are differentially produced during resistance responses to biotrophic pathogens and during susceptible responses to necrotrophic and hemi-biotrophic pathogens. Superoxide dismutase (SOD) is responsible for the catalysis of the dismutation of O2·-/ HO2· to H O , regulating the redox status of plant cells. Increased SOD activity has been correlated previously with resistance in barley to the hemi-biotrophic pathogen P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 90 publications
2
25
1
Order By: Relevance
“…The transgenic RNAi line, 161-7-11, has an approx. 4-fold reduction in transcript levels of CSD1 ( Lightfoot et al , 2017 ), whereas the mutant RPr 79/4 has an approx. 90 % reduction in leaf catalase activity ( Kendall et al , 1983 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The transgenic RNAi line, 161-7-11, has an approx. 4-fold reduction in transcript levels of CSD1 ( Lightfoot et al , 2017 ), whereas the mutant RPr 79/4 has an approx. 90 % reduction in leaf catalase activity ( Kendall et al , 1983 ).…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, barley nec1 mutants, which also show reduced RLS symptoms ( McGrann et al , 2015 b ), increased H 2 O 2 levels in response to pathogen inoculation ( Keisa et al , 2011 ). Furthermore, no effect on RLS symptoms was observed in the catalase-deficient mutant RPr 79/4 ( Kendall et al , 1983 ) or the HvCSD1 RNAi line ( Lightfoot et al , 2017 ; Fig. 7 ), both of which have reduced antioxidant levels potentially affecting foliar H 2 O 2 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, a secreted protein exhibiting sequence homology to a superoxide dismutase was identified in the secretome of A. solani HWC-168. It has been reported that the superoxide dismutase is involved in inhibiting oxidative damage of pathogens and plant resistance [ 37 , 38 ]. Furthermore, three trihydrophobins that are commonly found in the surface of aerial hyphae or fruiting body in fungi were predicted to be secreted [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study there was no significant difference in O 2 − , OH − , and H 2 O 2 before inoculation in resistant and susceptible genotypes, indicating a balanced production, utilization, and scavenging of ROS, under unstressed conditions. After inoculation with B. sorokiniana , O 2 − and OH − levels increased gradually in susceptible genotypes but not resistant ones, in which it eventually started decreasing as the genotypes appeared to balance the oxidative stress by the production of antioxidants such as superoxide dismutase and catalases involved in scavenging free radicals ( Lightfoot et al, 2017 ). This finding supports the idea that resistant genotypes are more successful at detoxifying O 2 − into less harmful substances such as H 2 O 2 , as part of the resistance response.…”
Section: Discussionmentioning
confidence: 99%